STATISTICAL APPROACH TO ESTIMATION OF LOGISTICAL RISKS OF INDUSTRIAL ORGANIZATIONS - Maria G. Polikarpova; Victoria V. Baryshnikova (Статистика и экономика)
The article offers the methodology of statistical research of the risks of logistical systems to improve the stability and efficiency of Russian industrial enterprises. Realization of this methodology is shown by the example of estimation of the risks of late shipment of goods of OAO Magnitogorsk Iron and Steel Works, JSC.